Fundamentals of Solid State Engineering - Razeghi, Manijeh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The fourth edition of this class-tested, multi-disciplinary introduction to solid state engineering adds dozens of revised and updated sections and problems, as well as three new chapters on solar energy harvesting, thermal and photothermal energy harvesting, and photo-thermovoltaics. Combining concepts from physics, chemistry, electrical engineering, materials science, and mechanical engineering, Professor Razeghi describes electron-electron and electron-phonon interactions, the Kane effective mass method, the carbon atom, thermal properties of crystals, the harmonic oscillator, the hydrogen atom, the quantum mechanical description of angular momentum, and the origin of spin in a chapter devoted to quantum mechanics. This textbook features an improved transport theory description that goes beyond Drude theory, discussing the Boltzmann approach. Introducing students to the rigorous quantum mechanical way of thinking about and formulating transport processes, this fourth edition presents the basic physics concepts and thorough treatment of semiconductor characterization technology, designed for solid state engineers. Enriches the text's multidisciplinary introduction to quantum mechanics, solid state physics, and advanced devices with coverage of two-dimensional semiconductors, thermal properties of crystals, and new chapters on systems for sustainable energy; Maximizes students' real-world knowledge with the most up to date developments in semiconductor physics and nano-engineering; Reinforces grasp of concepts presented with end of chapter problems; Elucidates computational aspects of solid state engineering with lucid, yet rigorous, mathematical derivations; Illustrates application to critical areas such as biophotonics and bioelectronics.
Electronic Structure of Atoms -- Introduction: the carbon atom -- Crystalline Properties of Solids -- Introduction to Quantum Mechanics -- Electrons and Energy Band Structures in Crystals -- Phonons and thermal properties -- Equilibrium Charge Carrier Statistics in Semiconductors -- Non-Equilibrium Electrical Properties of Semiconductors -- Semiconductor p-n and Metal-Semiconductor Junctions -- Optical Properties of Semiconductors -- Solar Energy Harvesting -- Thermal and Photothermal energy harvesting -- Photo-thermovoltaics -- Electron-Electron Interactions: Screening -- Semiconductor Heterostructures and Low-Dimensional Quantum Structures -- Quantum Transport -- Compound Semiconductors and Crystal Growth Techniques -- Semiconductor Characterization Techniques -- Defects -- Appendices.
Keywords: Electronics; Optical materials; Condensed matter; Spectrum analysis; Nanotechnology; Electronics and Microelectronics, Instrumentation; Optical Materials; Condensed Matter Physics; Spectroscopy; Nanotechnology